Enhancing Cargo ERP Implementation Efficiency through Agile Approaches - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
Enterprise Resource Planning (ERP) system implementation in the cargo logistics industry often needs help with challenges such as high costs, time delays, and gaps between business needs and system capabilities. Traditional approaches are often less responsive to change, leading to a lack of efficiency in cargo operations. This research aims to improve the efficiency of ERP implementation in the cargo logistics industry through an Agile approach. Research methods include literature analysis, interviews with industry experts, development of an Agile project plan, system testing, and evaluation of implementation results. Implementing the Agile approach in the cargo logistics industry has increased efficiency by reducing implementation costs, accelerating implementation time, increasing adaptability to change, and improving user satisfaction. This research contributes to developing best practices for ERP system implementation in the cargo logistics industry. The results can help cargo companies adopt a more adaptive and responsive approach, improve operational efficiency, and gain a competitive advantage in a competitive market.